Perancangan Layanan Elektronik Informasi Komersial Terpadu Kota Makassar - Kamisi, Anugrah Pratama; Syarif, Adi Chandra; Elisabeth, Elisabeth (TEMATIKA, Journal of Informatics and Information Systems, 2015)
One of the challenges faced by in managing information in a city is how to structure the various kind of data in many different forms to be easily access and shared among the coummunity. One important aspect of public service for a city is the accessibility of information. This research focuses on the design of a structured method which has several stages of analysis to solve the problem of the need for information about the city of Makassar. The results of this study to help the community in order to more easily obtain information about the datails ofMakassar city, and provide the opportunity for the agencies working together to promote their businesssKeywords: websites, Makassar city, information, electronic, service